Multiple Sclerosis Presents with Psychotic Symptoms and Coexists with Hypertrophic Cardiomyopathy. (13th August 2014) - Özcan, Muhammed Emin; İnce, Bahri and Karadeli, Hasan Hüseyin and Asil, Talip
Abstract : Multiple sclerosis (MS) is a demyelinating disease of the central nervous system. Psychiatric symptoms are not infrequent during MS, yet onset of MS with psychosis is rarely encountered. A 27-year-old Caucasian male was admitted due to numbness in his right arm and difficulty in walking. His clinical and laboratorial exams lead to the MS diagnosis. Nine months earlier, he also developed psychotic disorder, not otherwise specified (PD-NOS). His sudden onset of PD-NOS, his rapid and complete response to antipsychotics, and a relatively short interval between psychiatric and neurological signs indicate a high likelihood that PD-NOS was a manifestation of underlying MS. He also suffers from hypertrophic obstructive cardiomyopathy (HOCM). The patient's neurological complaints were recovered with methylprednisolone (1 g/day, i.v.) given for five days. Glatiramer acetate (1 × 1 tb.s.c.) was prescribed for consolidation and, after nine months of his admission, the patient fully recovered from neurological and psychiatric complaints. Interestingly, very recent studies indicate specific alpha-actinin antibodies in MS and alpha-actinin mutations cause HOCM. Thus, concurrence of MS with HOCM can be even a new syndrome, if further genetic studies prove.